Integration of Local Wisdom in Arabic Learning - Aflisia, Noza; Rini, Rini; Fikri, Ahmad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
To realize Arabic learning based on local wisdom, the vocabulary contained in the material should be directed to vocabulary related to local wisdom or the characteristics and potential of the region in the local area. This research aims to explain the forms of integration the local wisdom of Kerinci area in Arabic learning, both in listening, speaking, reading, and writing skills. So far, Arabic learning materials still expose vocabulary found only in Middle East Countries. For them who never seen and heard for the first time the vocabulary certainly feels strange, so it requires more treatment in giving understanding to students. This research is a library research through the stages of collecting data, identifying, understanding, analyzing, and determining. The results of this research indicate that to integrating the local wisdom of Kerinci region in Arabic learning can be done by modifying the content of the subject matter, which includes the forms of local wisdom possessed by Kerinci region in listening, speaking, reading, and writing. This is done so that the knowledge gained by students is not only in the mastery of Arabic vocabulary and grammar, but also in the knowledge of the natural surroundings such as, Kerinci Folk Songs, Kerinci Folk Stories, Kerinci Tourism, and so forth. So that sense of belonging and nationalism can be formed in the young generation who are Arabic learning.